Greetings from the Director of the Center of Excellence for Healthcare and Pharmaceutical Professionals - Juozas Ruolia, Director of Center of Excellence of Healthcare; Pharmacy Specialists (Slauga. Mokslas ir praktika, 2020)
Greetings from the Director of the Center of Excellence for Healthcare and Pharmaceutical Professionals.